BERKAH JAYA ELECTRIC SHOP APPLICATION IS BASED ON ANDROID - Andiani, Andiani; Nur, Siti Anzila (Jurnal Pilar Nusa Mandiri, 2024)
Berkah Jaya Electric Shop is a shop engaged in the sale of various kinds of electrical equipment. Goods sold by the store such as cables, sockets, and switches. The process of selling goods at the store is only done offline, namely by means of buyers coming directly to the store location. The process of managing store goods is still done by manually recording. This certainly causes problems such as the obstruction of buyers by time, and inefficient management of stock items. With this research, a sales application will be created that can make it easier for buyers to order goods, make product complaints, get information on the goods needed, and assist sellers in managing stock items and reports. This application will be built using the Waterfall method, utilizing the PHP, Laravel, and Kotlin programming languages. Making this application makes it easier for buyers to place orders via smartphones and sellers can more easily manage goods.